Improved Patient Dosimetry at Radioiodine Therapy by Combining the ICRP Compartment Model and the EANM Pre-Therapeutic Standard Procedure for Benign Thyroid Diseases - Andersson, Martin; Mattsson, Sören (Frontiers in Endocrinology, 2021)
Radioactive iodine is commonly used for the treatment of different thyroid conditions since the 1940s. The EANM has developed a standard pre-therapeutic procedure to estimate patient specific thyroid uptake at treatment of benign thyroid diseases. The procedure which models the time dependent fractional thyroid uptake is based on a two compartment fitting system, one representing the thyroid and the other the blood. The absorbed dose is however only estimated for the thyroid and not for any other organ in the body. A more detailed biokinetic model for iodine is given by the ICRP and includes an iodide transport in the whole body. The ICRP model has 30 different compartments and 48 transfer coefficients to model the biokinetics of iodide and to model different transfer for inorganic iodide and organic iodine. The ICRP model is a recirculation iodine model, and the optimization is performed on the whole model and not exclusively on the thyroid as in the EANM procedure. Combining the EANM method and the ICRP model gives both patient specific estimations of thyroid uptake and retention and include most organs in the body. The new software gives both an improved patient specific dosimetry for the thyroid and an estimation of the absorbed dose to non-target organs and tissues like kidneys, urinary bladder, stomach wall and uterus. Using the method described in this paper, the repercussions on the daily routines will be minimal.